OECD workshop consensus report: Ethical considerations with respect to human derived products, specifically human serum, in OECD test guidelines - Jacobs, Miriam N.; Bult, Jan M.; Cavanagh, Kevin; Chesne, Christophe; Delrue, Nathalie; Fu, Jianan; Grange, Emma; Langezaal, Ingrid; Misztela, Dominika; Murray, Jenny; Paparella, Martin; Stoddart, Gilly; et al. (Frontiers in Toxicology, 2023)
The ethical needs and concerns with use and sourcing of human materials, particularly serum, in OECD in vitro test guidelines were explored in a dedicated international workshop held in 2019. The health-related aspects of the donation procedure, including tissue screening, donor health, laboratory work health protection, permission from the donor for commercial use, payment of the donors and the potential for exploitation of low-income populations and data protection of the donors; supply, availability, and competition with clinical needs; traceability of the serum and auditability/GLP needs for the Test Guideline Programme, were examined. Here we provide the recommendations of the workshop with respect to the use of human serum, and potentially other human reagents, specifically with regard to test method development for OECD Test Guideline utility as part of the Mutual Acceptance of Data requirement across all OECD member countries. These include informed donor consent terminology, a checklist of human serum information requirements to be included with the Good Laboratory Practise report, and suitable sources for human serum to ensure waste supplies are used, that can no longer be used for medical purposes, ensuring no competition of supply for essential medical use.